Mixed Methods and Cross Disciplinary Research Towards Cultivating Eco-systemic Living - McIntyre-Mills, Janet; Romm, Norma R. A. (Contemporary Systems Thinking, 2019)
XXX, 464 p. 47 illus., 39 illus. in color.